AN EVALUATION OF THE NATIONAL INCOME RATIO AND EXTERNAL DEBT IN NIGERIA - Obianuju Adanna Ofodum; Mojekwu Ogechukwu Rita; Barisua Fortune Nwinee (Scholar Express Journal, 2025)
This study examined how external debt and external debt servicing affects the national income ratio in Nigeria, using gross domestic product (GDP) as the dependent variable to denote the national income ratio. The study employed time series data from 1992 to 2022. Data utilized in the study were sourced from the Central Bank of Nigeria statistical bulletin. The study employed the descriptive statistics, unit root, Johansen co-integration, and the VAR model. The study found that all the variables were integrated at fist difference, requiring the Johansen co-integration that invalidates the presence of long-run form among the variables. The VAR model showed that external debt significantly promotes GFP; whereas, external debt servicing retards GDP growth in Nigeria. The study concluded that external debt significantly stimulates the growth of the income level in Nigeria. The study recommended that the Nigeria's government should make sure that outside debt goes towards highly impactful, expansion-boosting initiatives. Loans for investments in areas like infrastructure, education, energy, and technology— which have the potential to provide long-term financial returns—should be given first priority by the government. Strong monitoring and evaluation systems for debt-funded initiatives will also guarantee responsibility and effectiveness. The government may promote economic development, raise GDP, and guarantee the long-term viability of borrowing by concentrating on efficient uses of outside debt
Keywords: Obligations; Growth; Output